PERSEPSI MASYARAKAT TERHADAP FUNGSI HUTAN MANGROVE DALAM UPAYA PENGURANGAN RISIKO BENCANA (Studi Kasus Lokasi Penelitian di Gampong Lamteh Kabupaten Aceh Besar dan Gampong Pande Kota Banda Aceh) - Said Khairullah; Indra .; Eldina Fatimah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
This thesis discusses the perception of society on the function of mangrove forest in the effort of disaster risk reduction. Perception is an internal process that allows us to face the environment, so the impact of disasters can be minimized. This research uses both qualitative and quantitative methods. Sources of data in this study consisted of primary data (field research) and secondary data (library research). The results of data analysis describe the perception of the community on the function of mangrove forest in the effort of disaster risk reduction from Gampong Pande Kota Banda Aceh and Gampong Lamteh, Aceh Besar District, with the number of respondents as many as 50 people. Community knowledge about the function of mangrove forest is very good. The community motivation of Gampong Lamteh in the management of Mangrove Forest area is good, while the people of Gampong Pande are very good. With a high level of motivation will affect the attitude and encourage the community to participate in maintaining and preserving the mangrove forest, this is visible from the attitude of both community of gampong to the conservation of mangrove forest which is very good, this means that both community of gampong involved in efforts to maintain and preserve the mangrove forest. Thus, people in Gampong Lamteh and Gampong Pande have a perception that mangrove forests are a common property so they feel entitled and responsible in managing and maintaining the sustainability of mangrove forests. The level of public perception of the mangrove forestsfunction is in the category of good and very good. The community understands that mangrove forest has many functions (ie compound function) as eco-tourism / ecotourism (social function), preventing flood / erosion (ecological function), place of income (economic function), and other functions.